PENGARUH KOMPLEKSITAS OPERASI PERUSAHAAN DAN KEPEMILIKAN PUBLIK TERHADAP AUDIT DELAY DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Ningsih, Riyanti Ratna; Shanti, Yunita Kurnia (LPPM Universitas Ibnu Sina, 2025)
This study aims to determine the effect of the complexity of company operations and public ownership on Audit Delay with company size as moderation. The population of this study uses Property and Real estate sector companies listed on the Stock Exchange in 2018-2022. This type of research is quantitative research with secondary data sources. Based on the purposive sampling method, a sample of 47 companies was obtained. The analysis method used is multiple linear regression analysis with data processing using the Eviews version 13 program. The results showed that the complexity of company operations and public ownership simultaneously had an effect on Audit Delay, while partially the complexity of company operations had no effect on Audit Delay, public ownership had a negative effect on Audit Delay, company size was unable to moderate the complexity of company operations on Audit Delay, and company size was able to moderate public ownership on Audit Delay